Yam (Dioscorea) husbandry: cultivating yams in the field or greenhouse - Mignouna, Hodeba D.; Abang, Mathew M.; Asiedu, Robert; Geeta, R. (Cold Spring Harbor Laboratory, 2009)
This protocol describes how to cultivate yams (Dioscorea) in the field or greenhouse. It refers especially to the tropical food species but it will also work for temperate species. The tropical food species of Dioscorea grow in warm, sunny climates with temperatures between 25ºC and 30ºC. Short days of 10-11 h result in tuber formation, while days longer than 12 h favor vine growth. Yams require deep, loose, textured loamy soil that is rich in organic matter. They are best planted at the beginning of the rainy season. Mulch around the planted sets protects them from excessive heat and desiccation, especially in areas with hot temperatures and dry weather. It also adds organic matter to the soil, prevents soil erosion, preserves water in the soil, and increases microbial activity in the soil. Yams do not tolerate waterlogged conditions. It is important to stake the plants to allow full exposure of their leaves to light for photosynthetic activity and to reduce disease.